Review and Analysis of the Literature: Artificial Intelligence-Based Digital Transformation of Automated Customer Onboarding - Vijay Thokal; Purushottam R. Patil (Engineering Proceedings)
Digital transformation in customer onboarding represents a paradigmatic shift in the way businesses engage with their clients. This process harnesses the power of digital technologies to create a seamless and highly efficient onboarding experience. The key objectives of digital client onboarding include saving time and effort, achieving cost savings and operational optimization, enhancing the overall customer experience, and ultimately increasing revenue. In the context of digital transformation customer onboarding, a wide array of digital tools and platforms are employed to facilitate the collection and processing of customer information. This enables the automation of previously manual procedures and allows businesses to offer personalized support throughout the onboarding journey. Compared to traditional customer onboarding methods, digital client onboarding offers several distinct advantages. Firstly, it saves valuable time and effort for both businesses and clients. The automation of various tasks, such as data entry and document verification, streamlines the onboarding process, allowing clients to quickly access the products or services they seek. This efficiency also translates into significant cost savings as businesses reduce overheads associated with manual processes, such as paperwork and administrative tasks. Furthermore, digital transformation in customer onboarding leads to a substantial improvement in the overall customer experience. Clients benefit from a faster and more convenient onboarding process, reducing the likelihood of frustration or abandonment. This enhanced experience fosters customer satisfaction and loyalty, ultimately contributing to increased revenue through repeat business and referrals.